2013 7th International Conference on Intelligent Systems and Control (ISCO) 2013
DOI: 10.1109/isco.2013.6481203
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency in sustainable development of Small and Medium Enterprises: An empirical study

Abstract: The Small and Medium Enterprises (SMEs) are an integral component of the Indian economy. SMEs consists of many energy intensive industries such as foundry, forging, steel re-rolling mills, glass and ceramics, bakeries, brick manufacture, food processing etc. The primary source of energy for these industries is coal, biomass, petroleum and electricity. Energy consumption in each of these industries is of high intensity and magnitude. Among them, the brick making units are generally confined to rural and semi-ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…EE motors use low loss materials (Saidur and Mahlia, 2009) and hence, their efficiency is 8% higher than standard motors (Zabardast and Mokhtari, 2008). Energy efficiency is vital for sustainable development as it enhances competitiveness through cost reduction and also minimises environmental degradation (Narasimha and Nagesha, 2013;Costa-Campi et al, 2015). Therefore, managements must explore the benefits of EE motors.…”
Section: Energy Conservation Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…EE motors use low loss materials (Saidur and Mahlia, 2009) and hence, their efficiency is 8% higher than standard motors (Zabardast and Mokhtari, 2008). Energy efficiency is vital for sustainable development as it enhances competitiveness through cost reduction and also minimises environmental degradation (Narasimha and Nagesha, 2013;Costa-Campi et al, 2015). Therefore, managements must explore the benefits of EE motors.…”
Section: Energy Conservation Opportunitiesmentioning
confidence: 99%
“…The electrical energy consumption in India during 2018-2019 was found to be 1,196,309 GWh (Central Electricity Authority, 2019) and industries consume 58% of it (Central Statistics Office, 2018). Improving energy efficiency is a useful strategy for enhancing competitiveness in energy-intensive SMEs (Narasimha and Nagesha, 2013). These improvements have multilevel benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of the high economic potential was highlighted in the case of active energy management in SMEs [43,44] and the implementation of a barrier's taxonomy regarding the adoption of energy-efficiency measures [45]. In addition, recent studies concluded that increasing energy efficiency could use the lean management concept at the SMEs level [46][47][48].…”
Section: Literature Reviewmentioning
confidence: 99%